The Content Analysis of the Georgian Left-Wing Internet Publications - Beridze, Giorgi (Politics / პოლიტიკა, 2019)
The study examines three Georgian leftist websites: the Anarchist Library, European.ge, and the Tbilisi Fabian Society. The Anarchist Library represents the interests of Georgian anarchists, while the other two have more social-democratic orientation. The research is relevant, because in recent years, the leftist groups from these internet platforms were the main participants of the frequent social protests. We can consider these websites as the tool for organization and the dissemination of ideas, and communication with broader society. The paper will conduct the content analysis of the publications displayed on these platforms, and will attempt categorize them and find the common context among them.